Some aspects of content-based instruction in english for economics students (on the basis of the teaching complex intelligent business) - Savichuk, Valentyna; Савічук, Валентина (Східноєвропейський національний університет ім. Лесі Українки, 2015)
Applying content-based instruction for teaching Business English to Economics students realizes the methodological paradigm declared by the European Framework on Foreign Languages.The tasks of the work are to analyze the ways CBI is realized by means of the teaching complex in ESPBE Intelligent Business. The author applied the critical analysis of literary sources, learning and summarizing the positive teaching experience, observation and test teaching. The performed analysis proves that CBI applied by the authors of Intelligent Business uses the foreign language as a means of teaching content, and the latter, in its turn, serves as a means of learning the foreign language. Having analyzed the teaching course Intelligent Business, we can see that by means of integrating all four basic speech skills the authors try to suggest their ways to form a high level of the communicative competence of students. In order to achieve this purpose the course models professionally authentic activities using authentic teaching materials with the selected topics and the logical grammar content, being oriented on maintaining the self -direction of students. Застосування методу, який базується на контенті для навчання ділової іноземної мови студентів економічних спеціальностей, реалізовує методологічну парадигму, обґрунтовану Загальноєвропейськими рекомендаціями з вивчення іноземних мов Ради Європи. Проаналізовано реалізацію методу СВІ засобами навчально-методичного комплексу з англійської мови для спеціальних цілей у галузі бізнесу та економіки Intelligent Business. При проведенні роботи застосовано критичний аналіз літературних джерел, вивчення та узагальнення позитивного досвіду викладання, спостереження та пробне навчання. Проведений аналіз доводить, що метод СВІ, застосований авторами комплексу Intelligent Business, використовує іноземну мову як засіб вивчення контенту/профільного матеріалу, а той, у свою чергу, є засобом вивчення іноземної мови.
Деякі аспекти навчання англійської мови, яке базується на контенті, студентів економічних спеціальностей (на базі навчально-методичного комплексу Intelligent Business).
Keywords: Content-based Instruction; English for Specific Purposes; Business English; навчання, яке базується на контенті; англійська мова для спеціальних цілей; ділова англійська мова